If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 + -1(4g + 5) = -11 Reorder the terms: 25 + -1(5 + 4g) = -11 25 + (5 * -1 + 4g * -1) = -11 25 + (-5 + -4g) = -11 Combine like terms: 25 + -5 = 20 20 + -4g = -11 Solving 20 + -4g = -11 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -4g = -11 + -20 Combine like terms: 20 + -20 = 0 0 + -4g = -11 + -20 -4g = -11 + -20 Combine like terms: -11 + -20 = -31 -4g = -31 Divide each side by '-4'. g = 7.75 Simplifying g = 7.75
| y=3y-3 | | (4xy-3xy)= | | -4+3x-6=-16 | | 7*(2x-5)=3*(2-5x) | | -5+3x-6=-16 | | 19x-4= | | 15k^2=25-10k | | 3+2x+6=-53 | | 5x-11= | | 3-x=-1 | | -(-2+4x)-(3-4x)+5=-(-3+6x)+x+1 | | -29+56= | | -4x-1+5x=-13 | | j/20=3 | | 3(x+8)=3x+24 | | x/4+2=-2 | | 22=6+2x | | k+4/2=k+9/2 | | (5x+4)(x-1)=2 | | k+4/2=k+9/4 | | -7x+2+4x=2 | | 40=12x+4 | | 2x-x+3+3x=x+13 | | -7x+2+5x=2 | | 6x^2+5x=-1 | | (2x-5)/3=(2-5x)/7 | | 22+x=12 | | 4(2x-8)=1/7(49x+70) | | 37g^8-37h^8= | | 19+x=2 | | x+x+16+3x=211 | | x^3+4x^2=7x+28 |